The agility model of digital companies: A cure for management ills? Some critical thoughts - FALL, Ibrahima (Revue Internationale de Psychosociologie et de Gestion des Comportements Organisationnels, 2020)
The digital revolution opens up new possibilities for workers to reappropriate their singularity, which is the true source of their genius and a stakeholder in their well-being. Indeed, competition through innovation has intensified with the rise of many start-ups, which in many fields have become real economic engines. The vision of the employee as a true source of value creation has become a key idea. Nevertheless, despite several decades of research on theories and practices of management as well as managerial innovations, it is clear that the Platonic vision of man as a measure of all things is negatively impacted.